X-shooter reveals powerful outflows in z ∼ 1.5 X-ray selected obscured quasi-stellar objects. Issue 3 (25th November 2014) - Brusa, M.; Bongiorno, A.; Cresci, G.; Perna, M.; Marconi, A.; Mainieri, V.; Maiolino, R.; Salvato, M.; Lusso, E.; Santini, P.; Comastri, A.; Fiore, F.; et al.
Abstract: We present X-shooter at Very Large Telescope observations of a sample of 10 luminous, X-ray obscured quasi-stellar objects (QSOs) at z ∼ 1.5 from the XMM -COSMOS survey, expected to be caught in the transitioning phase from starburst to active galactic nucleus (AGN)-dominated systems. The main selection criterion is X-ray detection at bright fluxes ( L X ≳ 10 44 erg s −1 ) coupled to red optical-to-near-infrared-to-mid-infrared colours. Thanks to its large wavelength coverage, X-shooter allowed us to determine accurate redshifts from the presence of multiple emission lines for five out of six targets for which we had only a photometric redshift estimate, with an 80 per cent success rate, significantly larger than what is observed in similar programs of spectroscopic follow-up of red QSOs. We report the detection of broad and shifted components in the [O iii ] λλ5007, 4959 complexes for six out of eight sources with these lines observable in regions free from strong atmospheric absorptions. The full width at half-maximum (FWHM) associated with the broad components are in the range FWHM ∼ 900–1600 km s −1, larger than the average value observed in Sloan Digital Sky Survey type 2 AGN samples at similar observed [O iii ] luminosity, but comparable to those observed for QSO/ultraluminous infrared galaxies systems for which the presence of kpc scale outflows has been revealed through integral field unit spectroscopy. Although the total outflow energetics (inferred under reasonable assumptions) may be consistent with winds accelerated by stellar processes, we favour an AGN origin for the outflows given the high outflow velocities observed ( v > 1000 km s −1 ) and the presence of strong winds also in objects undetected in the far-infrared.